2007
DOI: 10.1007/s11102-007-0030-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone assays: current methodologies and their limitations

Abstract: Measurement of circulating growth hormone (GH) concentrations is essential in diagnosis of either GH deficiency or GH excess. The invention of immunoassays for the measurement of peptide hormones was a major breakthrough, enabling the routine analysis of GH concentrations in larger series of samples. Over the last few decades, measurement technology has evolved from less sensitive, mainly radioactive assays based on polyclonal antisera to the latest generations of highly sensitive chemiluminescence methods emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 63 publications
0
36
0
3
Order By: Relevance
“…So, questions regarding an accepted gold standard remain. Further, standardized GH assays with appropriate quality control are critical for interpreting results [3,11,42]. Importantly, this aspect has not been given much attention to this point in time and merits consideration when relevant thresholds to guide clinical management are established.…”
Section: Discussionmentioning
confidence: 99%
“…So, questions regarding an accepted gold standard remain. Further, standardized GH assays with appropriate quality control are critical for interpreting results [3,11,42]. Importantly, this aspect has not been given much attention to this point in time and merits consideration when relevant thresholds to guide clinical management are established.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of measuring GH still lack standardization and the development of newer popular assays, including some monoclonal antibody-based assays, has demonstrated that there is significant variability among the results reported by different laboratories. The GH concentration reported in a specific patient's sample mainly depends on the method used by the laboratory [6]. Some measure only the 22 kD monomeric GH and others measure multiple isoforms of pituitary GH.…”
Section: Growth Hormone Assaysmentioning
confidence: 99%
“…It is known that several factors can influence the relationship between the level of GH and IGF-1, such as gender, age, liver disease, and malnutrition. IGF-1 and GH are known to have biological and technical limitations [3,4]. These facts influence long-term follow-up of acromegalic patients, as well as an early diagnosis of recurrence, and make them difficult.…”
Section: Introductionmentioning
confidence: 99%